Persepsi Mahasiswa Sejarah Terhadap Pembelajaran Daring Pada Program Studi Pendidikan Sejarah - Rehena, Matheos; Hetharion, Bety D.S.; Dokolamo, Hamid (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2023)
This study aims to examine the perceptions of students in the History Education Study Program regarding online learning conducted within the program. The research is descriptive and qualitative, employing an approach that seeks to explore the implementation of online learning deeply. Data collection techniques include interviews, observations, and document studies. The results of this study indicate that 95% of students expressed positive views on the implementation of online learning, meaning they encountered no significant challenges. In terms of students' perceptions of online learning, three points were measured: 1. Effectiveness: 90% of students had a positive perception, feeling that their ability to use technology had improved through online learning. 2. Communication: 60% of students had a negative perception, feeling that communication in online learning did not function well. 3. Feedback: 66% of students had a positive perception, indicating that the feedback and interaction between students and lecturers were effective. The challenges faced by students in online learning include internet connectivity issues, high costs, a heavy workload, an unconducive learning environment, and less effective teaching methods.